2022
DOI: 10.3390/su142114653
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Cell Types, Properties of Membrane, and Operating Conditions: A Review

Abstract: Fuel cells have lately received growing attention since they allow the use of non-precious metals as catalysts, which reduce the cost per kilowatt of power in fuel cell devices to some extent. Until recent years, the major barrier in the development of fuel cells was the obtainability of highly conductive anion exchange membranes (AEMs). On the other hand, improvements show that newly enhanced anion exchange membranes have already reached high conductivity levels, leading to the suitable presentation of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 211 publications
(282 reference statements)
0
10
0
Order By: Relevance
“…So, the definition of exergy is if one assumes that a system interacts with its surrounding environment, then the greatest theoretical work can be obtained from this system until this system and its surroundings reach a state of equilibrium [30]. Figure (6) elucidates the exergy efficiency for TEAC`s for the two cases, as mentioned in Table (4), and for all three intervals mentioned in Table (3). It can be observed that the degree of change in the thermoelectric air condition exergy efficiency when the power input supply to Peltier groups is (100+200) watts, as shown in Figure (6-a), ranges from a minimum value of (0.02%) to a maximum value of (0.55%) for 10 min, form a minimum value of (0.01%) to a maximum value of (0.34%) for 15 min, and form a minimum value of (0.01%) to a maximum value of (0.32%) for 20 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the definition of exergy is if one assumes that a system interacts with its surrounding environment, then the greatest theoretical work can be obtained from this system until this system and its surroundings reach a state of equilibrium [30]. Figure (6) elucidates the exergy efficiency for TEAC`s for the two cases, as mentioned in Table (4), and for all three intervals mentioned in Table (3). It can be observed that the degree of change in the thermoelectric air condition exergy efficiency when the power input supply to Peltier groups is (100+200) watts, as shown in Figure (6-a), ranges from a minimum value of (0.02%) to a maximum value of (0.55%) for 10 min, form a minimum value of (0.01%) to a maximum value of (0.34%) for 15 min, and form a minimum value of (0.01%) to a maximum value of (0.32%) for 20 min.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional air conditioning systems also contribute significantly to the amount of electricity consumed at homes in most countries [4]. It also contributes to global warming [5,6]; with relation to the greenhouse effect and the possibility of ozone depletion, there is significant CO2 released into the atmosphere because of the usage of conventional air conditioning systems [7]. The above problems can be overcome by thermoelectric air conditioning systems operated by solar photovoltaic panels (PV), which are environmentally friendly and more economical [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Whenever the electrodes were manufactured by squirting the catalyst ink on a cloth of carbon as GDL, the performance was obtained with around 830 mA⸳cm -2 at 600 mV [110]. Presently, the performance for PEMFC [115] exceeded 1000 mA⸳cm -2 . The MEA pressed with carbon cloth is well-studied [110].…”
Section: Role Of Feed Gas In Pemfcmentioning
confidence: 90%
“…Social acceptance and willingness to use associated technologies. The production, storage, and transport of green hydrogen are not without risks and impacts on the environment, society, and people [12]. A crucial aspect of the process of developing a GH value chain is the identification of potential sites for developments and their possible cumulative and indirect impacts, as the siting of facilities may directly trigger several additional risks and impacts addressed by other performance standards.…”
Section: Social Aspects Of Green Hydrogenmentioning
confidence: 99%